Photometric analysis of the eclipsing polar MN Hya - Wang, Qishan (2018)
As an eclipsing polar with a 3.39 h orbital period, MN Hya was going through a state change when we observed it during 2009-2016. Ten new mid-eclipse times, along with others obtained from literature, allow us to give a new ephemeris. The residuals of a linear fit show that period decreased during the phase of state change, which means angular momentum was lost during this phase. The associated X-ray observation indicates the mass accretion rate was about 3.6 x 10(-9) M(circle dot)yr(-1). The period decrease indicates that at least 60% of mass being transferred from the secondary was lost, maybe in the form of spherically symmetric stellar wind. In the high state, the data show the intensity of flickering reduced when the system had a higher accretion rate, and that flickering sticks out with a primary timescale of about 2 min, which implies the position of the threading point was about 30 white dwarf radii above its surface. The trend of light curves for the system in its high state follows that of the low state for a large fraction of the phase interval from phase 0 to phase 0.4 since, starting at phase 0.4, the cyclotron feature is visible, and the primary intensity hump of the light curves near phase 0.7 when the system is in the high state did not appear on the curve when it was in the low state. Those facts contradict predictions of the two-pole model.